2021
DOI: 10.1371/journal.pone.0247905
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the adaptive changes in the gut microbiome during standard-of-care chemoradiotherapy for gynecologic cancers

Abstract: Background A diverse and abundant gut microbiome can improve cancer patients’ treatment response; however, the effect of pelvic chemoradiotherapy (CRT) on gut diversity and composition is unclear. The purpose of this prospective study was to identify changes in the diversity and composition of the gut microbiome during and after pelvic CRT. Materials and methods Rectal swabs from 58 women with cervical, vaginal, or vulvar cancer from two institutions were prospectively analyzed before CRT (baseline), during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…Most studies evaluated the effect of ionizing radiation from a medical exposure (pelvic radiotherapy) [ 5 , 7 , 16 , 17 , 18 , 19 , 23 , 26 ], except the study of Sajjadieh et al, who conducted a study to evaluate the gut microbiota changes in 75 rural patients aged between 3 and 18 who lived in a contaminated area at a distance of 60 to 90 km from the Chernobyl Nuclear Power Plant and were exposed to natural environmental radiation and presented abdominal/gastrointestinal symptoms. Additionally, an older method of microbiome analysis, relying on bacterial culture colony-forming units, was used [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies evaluated the effect of ionizing radiation from a medical exposure (pelvic radiotherapy) [ 5 , 7 , 16 , 17 , 18 , 19 , 23 , 26 ], except the study of Sajjadieh et al, who conducted a study to evaluate the gut microbiota changes in 75 rural patients aged between 3 and 18 who lived in a contaminated area at a distance of 60 to 90 km from the Chernobyl Nuclear Power Plant and were exposed to natural environmental radiation and presented abdominal/gastrointestinal symptoms. Additionally, an older method of microbiome analysis, relying on bacterial culture colony-forming units, was used [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…also did not evaluate long-term effects. These are further limitations of these studies, given that the studies that had long-term evaluations reported gradual changes and significant differences in the follow-up sample [5,19,27].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations